17.5k views
3 votes
What is the simplified form of the following expression?


2 (\sqrt[4]{16x}) - 2 (\sqrt[4]{2y} ) + 3 (\sqrt[4]{81x} ) - 4 (\sqrt[4]{32y} )


User Tobyink
by
5.3k points

1 Answer

5 votes

We have


16=2^4\implies\sqrt[4]{16}=2


81=3^4\implies\sqrt[4]{81}=3


32=2^5\implies\sqrt[4]{32}=2\sqrt[4]{2}

So


2\sqrt[4]{16x}-2\sqrt[4]{2y}+3\sqrt[4]{81x}-4\sqrt[4]{32y}

is equivalent to


2^2\sqrt[4]{x}-2\sqrt[4]{2y}+3^2\sqrt[4]{x}-8\sqrt[4]{2y}

which reduces to


13\sqrt[4]{x}-10\sqrt[4]{2y}

User BlackWolf
by
4.7k points